Knowledge and Perceptions of Carbohydrates among Nutrition-Major and Nutrition-Elective Undergraduate Students in Canada. (17th February 2021) - Wang, Ye (Flora); Bellissimo, Nick; Kitts, David D.; O'Brien, Huguette Turgeon; David Ma, W. L.; Suh, Miyoung; Luhovyy, Bohdan; DiAngelo, Chiara; Pasut, Laura; Marsden, Sandra; Chung, Mei; Gurcan, Anil
Abstract: Objective: The purpose of the study was to assess knowledge and perceptions related to carbohydrates, including sugars, among Canadian nutrition-major undergraduates compared to those enrolled in elective nutrition courses (i.e., "nutrition-elective students"). Methods: Cross-sectional surveys were distributed during class time at eight Canadian universities, which included 32 questions on demographics, knowledge and perceptions of carbohydrates and sugars. Descriptive analyses were performed. Differences between groups were tested by Chi-squared statistics. Results: A total of 1207 students (60% nutrition-majors) participated in the survey (January 2016–February 2017). Internet-based sources accounted for one-third of the sources where students obtained nutrition information. About 61% of internet-bases sources were "online" or "website" with no qualifiers, and about a quarter was from social media. A higher percentage of nutrition-majors correctly answered knowledge questions of carbohydrates compared with nutrition-elective students ( p < 0.01); no difference was observed for sugars-related knowledge questions. The perceptions of sugars were generally negative and did not differ between groups. Conclusions: Several knowledge gaps and common perceptions on topics related to carbohydrates and sugars were identified; nutrition-major students performed better than nutrition-elective students on carbohydrate knowledge questions, but not sugars. These results highlight the importance of identifying methods to help students bridge knowledge gaps and develop skills to critically evaluate nutrition information from various resources and challenge personal biases.